Memory about Lithuanians deportees in contemporary Russia - Flige, Irina (Genocidas ir rezistencija, 2008)
GULAG and ‘Soviet terror’ are among the most important concepts for understanding modern Russia and its history. GULAG has become part of the culture and life of modern society. However, the memory of GULAG and terror has not become an integral part of the nation’s memory. The memory of GULAG is practically not anchored in the public consciousness as part of the national experience. There are no national programmes dedicated to this memory, and the subject of terror and GULAG is almost completely absent from general education and higher education history courses. There has never been a public debate about the past in Russian society. Nevertheless, the memory of terror is manifested in one form or another in contemporary Russian culture. However, we deliberately do not deal with such important aspects of it as historical research, the philosophical or theological making sense of the GULAG experience, the teaching of history in secondary and tertiary education, and its reflection in literature, film, theatre and television. Among them are memorial signs commemorating Lithuanian victims.
Keywords: Russia; Lithuania; deportations; memory